Breast metastasis in a young pregnant woman affected by metastatic melanoma - Pagliara, Martina Pia; Gorgoglione, Annalisa; Talamo, Vincenza; Paparella, Maria Teresa; Palladino, Nicola; Castelvetere, Marina; Serricchio, Ettore Angelo; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2023)
Metastasis to the breast from extramammary tumors are rare, and the most common cancer that metastasizes to this site is malignant melanoma (MM). Unfortunately, metastases from malignant melanoma reveal a widespread of the disease and a high likeliness of poor diagnosis. In this study, a case of left breast metastasis of MM in a young pregnant woman, with a fast progression of the mammary and systemic course of pathology and unfortunately poor prognosis is presented. Despite the role of pregnancy in MM has yet to be unraveled, our study encourages the theory that immunosuppression and hormonal changes due to pregnancy may aggravate melanoma prognosis.